Clinico-pathological correlation between deep vein thrombosis and malignancy - Chhabhaya, Nirav; Patel, Jayesh; Bhatt, Ravi; Agarwal, Chetan (International Surgery Journal, 2023)
Background: Cancer is one of the risk factors with estimates suggesting annual incidence of venous thrombo-embolism (VTE) is 0.5% in cancer patients compared to 0.1% in the general population. VTE is the second most common cause of death from cancer. Cancer associated thrombosis (CAT) is the target of intense interest in recent medical literature, including its epidemiology, pathophysiology, challenges in diagnosis, prophylaxis and treatment. Cancer types, stages, treatment and comorbidities are among the risk factors for developing VTE. Methods: This was a retrospective study based on patient hospital records from May 2017 to Dec 2021. About 50 patient records reportedly having CAT were studied to meet research objectives. Data pertaining to patient age, gender and comorbidity was collected for study purpose. Patients having confirmed diagnosis for deep venous thrombosis (DVT) (Duplex scan) and malignancy (Biopsy) were considered to ensure data completeness for analysis and reporting. Results: Our study showed that there was no correlation between different types of cancer with deep venous thrombosis, neither with different approach of treatment had it showed any significant results nor with any comorbidity. But we found out a correlation between different cancer with various comorbidity. Conclusions: Our study aimed at exploring clinical and pathological correlation between DVT and malignancy. Our study was a sincere effort to study clinic-pathological correlation among cancer patients with known cases of venous thrombosis. Further studies are warranted with large sample and more extensive case record format, and preferably long-term follow-up to understand patient outcome.